International Handbook of Health Literacy Research, practice and policy across the lifespan - Okan , Orkan; Bauer , Ullrich; Levin-Zamir, Diane; Pinheiro , Paulo; Sørensen, Kristine (Policy Press, 2019)
Available Open Access under CC-BY-NC licence. Health literacy addresses a range of social dimensions of health, including knowledge, navigation and communication, as well as individual and organizational skills for accessing, understanding, evaluating and using information. Particularly over the past decade, health literacy has globally become a major public health concern as an asset for promoting health, wellbeing and sustainable development.